O ENSINO DE INGLÊS NA EDUCAÇÃO INFANTIL: PRÁTICAS PEDAGÓGICAS EM ESCOLAS DO MUNICÍPIO DE GUARAPUAVA – PR - BORTOLOTTI, FERNANDA SEIDEL (2020)
The present research is situated in the educational area, relying on applied linguistics and educational linguistics theoretical approaches, and it was meant to answer how English teaching takes places at early childhood education (ECE) in Guarapuava - PR, being its aim the analysis of the different pedagogical practices adopted to teach English in the basic education in this city. The Cultural-Historical Theory (VYGOTSKY, 2012), the conception of language as a social phenomenon (BAKHTIN, 2011), of bilingual education (GARCÍA; WOODLEY, 2014) and of translanguaging (GARCÍA; FLORES, 2012; BUSCH, 2014) were applied to support this paper. The first specific objective was quantitative, presenting the scenario of the English language education offer to these children. Other than that three qualitative specific objectives were proposed: to identify the pedagogical practices at the participant schools, its common points and differences; to discuss the accordance of the practices and the development of the children; and to provide reflections about the practices and their implication to teacher education. The study begins with a bibliographic review of legislations, researches and English teaching at ECE performances, in international, national, regional and local terms. When it comes to methodology, it involves the contact with the schools for the quantitative survey, as well as the observations, interviews, questionnaires and documentary analysis for the qualitative. As a non-overall analysis of the city, a study case was conducted based on triangulation of data. There were 63 municipal schools and 26 private involved, from which 17 had the initiative to offer English at ECE, all of them private schools. For the qualitative analysis school A (private, 4 years old group) and B (public, attended by a volunteer project of language school C, 5 years old group) were invited to participate represented by its teachers. To analyze the practices 9 categories were adopted: syllabus; courseware, methods and practices; languages usage; influence of external participants; corrections; difficulties; eases and opinion about the field. The considerations obtained through this research were presented at the end, contributing from the classroom practices, supporting the teaching and the education of the teachers, to the extension of public policies, mobilizing the promotion and enlarging the offer of English at ECE. The survey about the offer in the city posits the variance between private and public schools, that being so the public school could only be analyzed due to a volunteer program holding it. The established categories show evidence of accordance and distinctions between school A and B, discrepancies that seem related to the lack of specific lawmaking, being this absence reflected also in the appropriateness of the pedagogic manner regarding children development and the teacher education. In addition, the weaknesses of this paper and suggestions to further ones were indicated, bearing in mind the development of the field and naming the main biases of English teaching at ECE.